The impact of adjuvant radiotherapy for cosmetic results after immediate breast reconstruction based on the tissue expander and permanent implant - Zh. V. Bryantseva; S. N. Novikov; D. G. Ulrikh; P. V. Krivorotko; I. A. Akulova; T. S. Yaganova; T. T. Tabagua; K. Yu. Zernov (Опухоли женской репродуктивной системы)
Background. One of the causes of complications in breast cancer patients after immediate breast reconstruction (IBR) is postmastectomy radiation therapy (PMRT).Aim. Retrospective analysis of the results of IBR, and evaluating the effect of PMRT on the frequency and type of complications.Materials and methods. Between 2015 and 2021, 798 patients underwent IBR with tissue expander or implant in N.N. Petrov National Medical Research Center of Oncology, Ministry of Health of Russia. PMRT was performed in 375 patients (group 1). The remaining 423 patients did not receive PMRT (group 2). Complications, including reconstructive failure (RF), Baker grade III/IV capsular contracture (CC), were recorded and analyzed.Results. Finally, cosmetic result analyzed in 521 patients. In 281 patients of PMRT group (group 1) IBR with expander or implant were performed in 144 and 137 cases, respectively. In the 240 patients without PMRT (group 2), IBR with expander was performed in 81 patients, with implant – in 159 cases. Pooled analysis revealed that overall rate of complications in the PMRT group was 33.8 % (in 95 of 281 patients), in non-irradiation patients – 22.9 % (in 55 of 240 patients), p <0.01. In group 1, RF were recorded in 67 (23.8 %) patients, in group 2 – in 44 (18.3 %) patients, p >0.05. CC in group 1 were detected in 28 (10 %) patients, in group 2 in 11 (4.6 %) patients, p <0.05. In patients with permanent implants RF were detected in 21 (14.6 %) of irradiation patients and in 22 (13.8 %) non-irradiation patients (p >0.2). On the contrary, CC were mentioned in 22 (16.1 %) of irradiated patient and in 8 (5 %) patients that didn’t receive PMRT, p <0.005. After reconstruction with expander RF were diagnosed in 46 (31.9 %) patients after PMRT and in 22 (27.2 %) non-irradiation patients, p >0.2. CC were observed in 6 (4.2 %) patients from PMRT group and in 3 (3.7 %) patients treated without PMRT, p >0.2.Conclusion. PMRT in patients after IBR with simultaneous installation of a permanent implant is characterized by a decrease in the incidence of RF, but an increase in the incidence of CC.